Twenty-five years using reclaimed water to irrigate a golf course in Gran Canaria - Estevez, E.; Cabrera, M. C.; Fernandez-Vera, J. R.; Hernandez-Moreno, J. M.; Mendoza-Grimon, V.; Palacios-Diaz, M. P. (Spanish Journal of Agricultural Research, 2010)
Low focus in water management and short time data availability are the main limiting factors for reclaimed water project analysis. One of the oldest Spanish golf courses with a medium period of available data was selected to study and describe the medium time effects (25 years) on soil and aquifer as a consequence of reclaimed water reuse, and to compare the experimental results with reclaimed water quality criteria under a sustainability point of view. An excess of reclaimed water (83%) is used for this golf course irrigation in spite of the high water price (€ 0.4 m–3). The excess water reduced the risk of substances accumulation in soils, but for several of them the foresaid excess increased the possibility of polluting the aquifer (nitrates). Experimental data confirmed sustainability water quality criteria which predicted phosphorus and boron accumulation in soil. Soil characteristics and water management have to be also considered as critical factors to explain water quality effects in land and environmental conditions.